The top 10 research priorities in cystic fibrosis developed by a partnership between people with CF and health care providers - Rowbotham, Nicola J.; Smith, Stuart J.; Leighton, Paul; Rayner, Oliver C.; Gathercole, K.; Elliott, Z.C.; Nash, Edward F.; Daniels, T.; Duff, A.J.A.; Collins, S.; Chandran, S.; Peaple, U.; et al. (BMJ Publishing Group, 2017)
There remain many treatment uncertainties in cystic fibrosis (CF). With limited resources, research should focus on questions which are most important to the CF community. We conducted a James Lind Alliance Priority Setting Partnership in CF. Research questions were elicited and then prioritised in successive surveys. A workshop agreed the final Top 10. Online methods avoided cross infection and widened participation. The elicitation survey had 482 respondents (1080 questions) and prioritisation survey 677 respondents. Participants were drawn equally from the patient and clinical communities globally. We have achieved a consensus on ten research priorities which will be attractive to funders.